2022
DOI: 10.1155/2022/4877708
|View full text |Cite|
|
Sign up to set email alerts
|

Surgical Treatment of Hand and Foot Gout Stone and Influence Factors on Prognosis

Abstract: Purpose. To explore the technique of surgical treatment of hand and foot gout stone by using 3D CT reconstruction images and influence factors on prognosis. Method. 48 cases of hand and foot gout were treated surgically and retrospective analyzed. Before operation, we used 3D CT reconstruction images to check the accurate site and amount of uric acid (white chalk foam) deposition. Different surgical methods were applied depending on the different deposition site of urine acid stone. The frequency of gout attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In the second method, the eroded superficial flexor tendon of the finger is excised, and the wrist is rinsed with normal saline. The doctors who choose this method believe that lost postoperative function of the superficial flexor tendon of the affected finger can be compensated by the deep flexor tendon of the affected finger, and there may be no dysfunction of hand activity [ 9 ]. Based on the results of this study, the author believes that for carpal tunnel syndrome caused by tophi, selective resection of the superficial flexor tendon of the affected finger will not have a great impact on the postoperative function of the affected finger.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the second method, the eroded superficial flexor tendon of the finger is excised, and the wrist is rinsed with normal saline. The doctors who choose this method believe that lost postoperative function of the superficial flexor tendon of the affected finger can be compensated by the deep flexor tendon of the affected finger, and there may be no dysfunction of hand activity [ 9 ]. Based on the results of this study, the author believes that for carpal tunnel syndrome caused by tophi, selective resection of the superficial flexor tendon of the affected finger will not have a great impact on the postoperative function of the affected finger.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, due to the improvement of quality of life, gouty carpal tunnel syndrome caused by hyperuricaemia is also increasing year by year and becoming more prevalent in younger age groups [ 8 ]. The clinical treatment of gouty carpal tunnel syndrome is divided into medical treatment and surgical treatment; medical treatment can control the gout attack and relieve the disease but cannot eliminate the deposited gout stones [ 7 , 9 , 10 ]. Gouty carpal tunnel syndrome can occur with carpal osteonecrosis, rupture of the intercarpal ligament, wrist instability and carpal stiffness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%